Osteoradionecrosis in osseous free flaps after maxillofacial reconstruction: a single-center experience - Fenske, Jakob; Lampert, Philipp; Nikolaidou, Eirini; Steffen, Claudius; Beck, Marcus; Neckel, Norbert; Nahles, Susanne; Heiland, Max; Mrosk, Friedrich; Koerdt, Steffen; Rendenbach, Carsten (Frontiers in Oncology, 2025)
ObjectiveIn the multimodal treatment of advanced head and neck malignancies, primary free flap reconstruction in a one stage procedure with tumor resection is frequently combined with adjuvant radiotherapy. Radiotherapy is known to exhibit side effects on transplanted free flaps, including osteoradionecrosis (ORN) of native and transplanted bone. This study aims to evaluate the therapeutic outcomes and potential predictors of free flap ORN within osseous free flaps based on a large-scale, single-center database.MethodsA retrospective analysis was conducted on patients who underwent osseous free flap reconstruction of maxilla or mandible in a one stage procedure followed by adjuvant radiotherapy due to an advanced head and neck malignancy between April 2017 and July 2023. After case matching, patients with and without free flap ORN were assessed for potential predictors using univariate and multivariate analysis.Results112 patients met the inclusion criteria. 21 patients (19%) developed ORN within the free flap. Following case matching, 42 patients (10 females, mean age 61.5 ± 9.1 years) were included in the final analysis. The mean time to ORN diagnosis was 19 (7–56) months after surgery. Total flap loss occurred in 7 patients (33%) following flap ORN. Smoking (76% vs. 38%; OR 5.78; p=0.03) and prior plate exposure (67% vs. 24%; OR 5.61; p=0.03) emerged as robust predictors of flap ORN in uni- and multivariate analysis.ConclusionOsseous free flap ORN is a severe radiooncologic complication, often resulting in total flap loss and subsequently increased morbidity. Smoking and prior plate exposure were identified as key predictors of flap ORN development. Individual risk assessment and careful evaluation of osseous free flap irradiation must be evaluated in future radiooncological concepts.